Impact of learning management blog on students’ language learning and acquisition - Nafiseh Zarei; Supyan Hussin (Penerbit UKM, 2014)
In the modern language learning scenario, language learning and language acquisition experience can be enriched outside the classroom where students can engage in interactive activities. This is enabled by Web 2.0 tools such as blog, twitter, and computer mediated communication tools like email and chat. Web 2.0 tools can unlimited space and time for students. Blog as one type of Web 2.0 tools can be designed to manage the learning and acquisition environment which provides learning materials, relevant learning resources, and online discussion. This paper reports on the impact of a “Learning Management Blog” (LMB) environment on students’ experience of language learning and language acquisition. The LMB was designed to function as a language learning platform for a particular group of tertiary students. Supplementary course materials that matched the objectives of the course were uploaded to the LMB. This qualitative study involved 30 Malaysian undergraduate ESL students at local university. A semi-structured interview was carried out to elicit responses from the students; then the recorded data were transcribed and analyzed qualitatively. The findings of the study revealed that the LMB has proven to be a useful tool to facilitate the language learning and language acquisition processes among the participants. The students had opportunities to use the language learning materials in the LMB as well as interacting with each other in the discussion forum. The learners developed their independent learning interest and motivation to use the English language learning materials and participate in the LMB environment.